Recurrent Stress Cardiomyopathy: A Rare Variant in a Young Patient with Undiagnosed Pheochromocytoma - Robert Lembo; Paul Wesley; Joe B. Calkins (Case Reports in Cardiology)
Biventricular stress cardiomyopathy is one of several known anatomical variants of reversible cardiomyopathies to occur. We present a case of a young patient with recurrent stress cardiomyopathy complicated by cardiogenic shock in the perioperative period. The cardiomyopathy observed was in a patient with neurofibromatosis type I and undiagnosed pheochromocytoma who presented for intervention of hydrocephalus. This case demonstrates the importance of vigilance in the young patient who develops shock in the perioperative period.